The tumor or inflammation? a case report on primary pulmonary choriocarcinoma - Wang, Na; Zhang, Nan; Zhang, Xinyue; Wang, Yuanyuan; Fu, Yajie; Guo, Lingfei; Liang, Changhu; Yu, Mengru (Frontiers in Oncology, 2023)
Choriocarcinoma is a rare malignant germ cell neoplasm with high invasiveness, the majority of which are pregnancy-related, and the female genital tract is the most prevalent site of the disease. Although early-stage choriocarcinoma typically metastasizes to the lungs, primary pulmonary choriocarcinoma is extremely rare. Primary pulmonary choriocarcinoma is difficult to diagnose, and it progresses rapidly. Combined with the difficulty of treatment, the prognosis of patients is generally poor. In this article, we retrospectively analyzed a case of female primary pulmonary choriocarcinoma, combined with a review of literature, to understand and describe the diagnostic and treatment progress of PPC.